(3NdGUI GdCbhGd aj eYQaI GdhbJ hQDjI GdgdGds - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI gPg QSGdg eNJUQg efbMI eMQQI ai GdYed HGdQHY GdeLjH SejJgG HNdGUI GdCbhGd s
(3BNQgG (B:s
(3aYdjg HcJGHfG GdeSei HGdLGeY GdeajO ai GdcTa Yf CUhd eSGFd GdJbhje hGdehGdjO , hdjchf Pdc BNQ eG CQOfGg ef gPg GdQSGdI s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B128 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B32 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B183) s
(3JHUQI GdJQGLe(Bs
Keywords: (3Gdadcs